Low-shrinkage self-reinforced degradable bone cement as well as preparation method and application thereof
By using cyclic monomers, hydrophilic vinyl monomers, crosslinkers and inorganic fillers in bone cement materials, and through redox reaction and free radical ring-opening polymerization, the problems of high shrinkage, non-degradation and no osteogenic activity of bone cement materials are solved, and low shrinkage, low exothermic, high strength and degradability are achieved. It is suitable for orthopedic and dentistry applications.
Patent Information
- Application Number
- CN202411921566.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-14
AI Technical Summary
The existing bone cement materials have problems such as high shrinkage, non-degradation, and no osteogenic activity, which leads to thermal damage to bone tissue, poor binding and unfavorable bone regeneration.
Low shrinkage self-enhanced degradable bone cement is used, and its preparation raw materials include liquid phase components and solid phase components. The liquid phase components include cyclic monomers, hydrophilic vinyl monomers, crosslinking agents and reducing agents. The solid phase components include inorganic fillers and initiators. Through redox reactions and free radical ring-opening polymerization, the shrinkage rate and exothermic heat of the material are reduced, and its degradability and osteogenic activity are improved.
It achieves low shrinkage, low heat exothermic, high strength and degradability, and has good osteogenic activity. It is suitable for orthopedic and dentistry applications, avoiding the thermal damage and poor binding problems of traditional bone cement materials.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials, and in particular relates to a low-shrinkage self-reinforced degradable bone cement and a preparation method and application thereof. Background Art
[0002] Bone cement is a medical material used in orthopedic surgery. It is widely used in bone injury diseases such as compression fractures caused by osteoporosis, vertebral burst fractures caused by trauma, and joint surgical fixation. Bone cement usually includes solid powder and liquid components. After mixing them into a slurry in a certain proportion at room temperature, it is injected into the complex and irregular bone defect site and solidified after the dough period.
[0003] At present, bone cement mainly includes two categories: organic bone cement such as polymethyl methacrylate (PMMA) and inorganic bone cement such as calcium phosphate.
[0004] Among them, PMMA bone cement is a bone cement composed of powder and liquid. Although it is widely used, it has the following problems: ① High shrinkage rate: PMMA bone cement is formed by in-situ polymerization of vinyl monomers. The volume gradually shrinks during the curing process, accompanied by a large amount of heat release, which not only causes thermal shrinkage, but also causes irreversible thermal damage to the surrounding bone tissue; ② Non-degradable: The PMMA carbon-carbon main chain is not biodegradable, resulting in poor integration of bone cement materials with bones and hindering new bone formation. Long-term implantation can easily lead to aseptic loosening; ③ No osteogenic activity, cannot form an organic chemical interface with the host bone tissue, and cannot induce bone growth in the defect site, which is not conducive to regeneration and healing with bones.
[0005] Calcium phosphate bone cement is generally formed by adding two or more calcium phosphate powders to a liquid phase blending agent and then hydrating and solidifying to form bone cement similar to the structure of human bone tissue. This material also has some shortcomings, such as: low mechanical properties, easy disintegration, difficulty in applying to weight-bearing parts, and too fast degradation rate. Therefore, it is urgent to develop a new type of bone cement material that has the characteristics of low volume shrinkage, low heat release, high strength, and is degradable and has good osteogenic activity. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a low shrinkage self-reinforced degradable bone cement and a preparation method and application thereof. The bone cement has low shrinkage, high strength and degradability, low heat release and good osteogenic activity, and has important application value in orthopedics and stomatology.
[0007] To achieve this purpose, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a low-shrinkage self-reinforced degradable bone cement, the raw materials for its preparation include a liquid phase component and a solid phase component;
[0009] The liquid phase components include cyclic monomers, hydrophilic vinyl monomers, crosslinking agents and reducing agents; and the solid phase components include inorganic fillers and initiators.
[0010] Preferably, the ratio of the mass of the inorganic filler to the volume of the liquid phase component is (0.1~5):1 g / mL.
[0011] Preferably, the molar ratio of the initiator to the reducing agent is (0.1-1):1.
[0012] Preferably, the molar ratio of the hydrophilic vinyl monomer, the crosslinking agent, the reducing agent and the cyclic monomer is (0.01-10):(0.001-0.1):(0.001-0.1):1.
[0013] More preferably, the ratio of the mass of the inorganic filler to the volume of the liquid phase component is (0.5~2):1 g / mL.
[0014] More preferably, the molar ratio of the initiator to the reducing agent is (0.5~1):1.
[0015] More preferably, the molar ratio of the hydrophilic vinyl monomer, the crosslinking agent, the reducing agent and the cyclic monomer is (0.5-3):(0.005-0.05):(0.005-0.05):1.
[0016] Preferably, the cyclic monomer includes, but is not limited to, any one or more of 2-methylene-1,3-dioxepane, allyl sulfone macrocyclic monomer, 5,6-benzo-2-methylene-1,3-dioxepane or spiro-o-carbonate.
[0017] Preferably, the hydrophilic vinyl monomer includes, but is not limited to, any one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate or poly(ethylene glycol) methacrylate.
[0018] Preferably, the reducing agent includes, but is not limited to, any one or more of tertiary amine reducing agents such as N,N-dimethylaniline, N,N-trimethylaniline, and N,N-dimethyl-p-toluidine.
[0019] Preferably, the initiator includes, but is not limited to, any one or more of organic peroxides such as benzoyl peroxide, tert-butyl benzoyl peroxide, dibenzoyl peroxide, and diisophorone peroxide.
[0020] Preferably, the crosslinking agent is a monomer containing two or more vinyl units.
[0021] Preferably, the inorganic filler is any one or more of an inorganic salt containing magnesium / calcium elements, an oxide containing magnesium / calcium elements, or bioactive glass.
[0022] Preferably, the cross-linking agent includes but is not limited to any one or more of polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, diacrylamide polyethylene glycol, dimethacrylamide polyethylene glycol, dimethacrylate phosphate or diacrylate phosphate.
[0023] Preferably, the inorganic filler includes, but is not limited to, any one or more of β-calcium phosphate, α-calcium phosphate, amorphous calcium phosphate, calcium hydrogen phosphate, calcium oxide, overburned magnesium oxide, magnesia-type magnesium phosphate, amorphous magnesium phosphate, bioactive glass, potassium dihydrogen phosphate or diammonium hydrogen phosphate.
[0024] Preferably, the shrinkage rate of the bone cement after curing is 0.1-10%, and the degradation rate after 3 months in phosphate buffered saline is 18.7%-26.9%.
[0025] In a second aspect, the present invention provides a method for preparing the above-mentioned low shrinkage self-reinforced degradable bone cement, comprising the following steps:
[0026] The liquid phase component and the solid phase component are mixed and solidified in situ to obtain bone cement.
[0027] In a third aspect, the present invention provides an application of the low shrinkage self-reinforced degradable bone cement in the preparation of bone cement products.
[0028] Preferably, the bone cement product is filled into the bone injury site during the injection period.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The present invention provides a low shrinkage self-reinforced degradable bone cement, and the raw materials for preparing the bone cement include a liquid component and a solid component; the liquid component includes a cyclic monomer, a hydrophilic vinyl monomer, a cross-linking agent and a reducing agent; the solid component includes an inorganic filler and an initiator. After the liquid component and the solid component are mixed, the reducing agent in the liquid component and the initiator in the solid component undergo a redox reaction, and in the system of the redox reaction, the cyclic monomer undergoes free radical ring-opening polymerization, and the chemical bond is broken and the ring is opened, so that the intermolecular distance caused by the polymerization of the hydrophilic vinyl monomer is shortened, the material shrinkage rate is reduced, and the interface loosening problem caused by the volume shrinkage after the bone cement is polymerized is effectively avoided, and the reaction exotherm is reduced. Because the main chain contains an ester bond structure after the free radical polymerization, the bone cement has a degradable and absorbable characteristic ring-opening polymerization. In the present invention, the introduction of the hydrophilic vinyl monomer enables the bone cement to significantly improve its cell affinity and bone integration ability compared to the fully hydrophobic material, and at the same time, the moderate hydrophilicity is conducive to promoting the hydrolysis and degradation process after the integration of the bone cement. At the same time, inorganic fillers can be evenly dispersed between the polymer networks, further resisting the shrinkage caused by polymerization through the filler effect. In addition, inorganic fillers can undergo hydration and curing reactions. In a humid in vivo environment, they can form a skeleton in the cross-linked copolymer to maintain the mechanical properties or even improve the mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a comparison chart of the shrinkage rate of the bone cement obtained in Comparative Examples 1-2 and Examples 1-4;
[0032] Figure 2 The figure is a comparison of the mechanical properties of the bone cements obtained in Comparative Examples 1-2 and Examples 1-4;
[0033] Figure 3 The figure is a comparison chart of the in vitro degradation rates of the bone cements obtained in Comparative Examples 1-2 and Examples 1-4;
[0034] Figure 4 The osteogenic activity comparison chart (OCN) of the bone cement obtained in Comparative Examples 1-2 and Examples 1-4;
[0035] Figure 5 This is a comparison chart of the osteogenic activity (OPN) of the bone cements obtained in Comparative Examples 1-2 and Examples 1-4. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0037] The invention provides a low-shrinkage self-reinforced degradable bone cement, the preparation raw materials of which include a liquid phase component and a solid phase component, which are mixed and then solidified.
[0038] In the present invention, the liquid phase components include cyclic monomers, hydrophilic vinyl monomers, crosslinking agents and reducing agents; and the solid phase components include inorganic fillers and initiators.
[0039] In the present invention, the cyclic monomer can be subjected to free radical ring-opening polymerization under a redox initiation system, and the chemical bond is broken and the ring is opened, so as to reduce the shortening of the intermolecular distance caused by the polymerization of the vinyl monomer into bonds, effectively avoiding the problem of interfacial loosening caused by the volume shrinkage after the polymerization of the bone cement, and reducing the heat release of the reaction. Since the main chain obtained after the free radical polymerization contains an ester bond structure, the bone cement has the characteristics of being degradable and absorbable. Specifically, the cyclic monomer includes but is not limited to any one or more of 2-methylene-1,3-dioxepane (MDO), allyl sulfone macrocyclic monomer (MAS), 5,6-benzo-2-methylene-1,3-dioxepane (BMDO), and spiro-o-carbonate (SOC), preferably allyl sulfone macrocyclic monomer MAS. Specifically, the structural formulas of the above-mentioned several cyclic monomers are as follows:
[0040] .
[0041] In the present invention, the selected vinyl monomer is hydrophilic because the introduction of the hydrophilic vinyl monomer enables the bone cement to significantly improve its cell affinity and bone integration ability compared with the fully hydrophobic material, and at the same time, moderate hydrophilicity is conducive to promoting the hydrolysis and degradation process of the bone cement after integration. The hydrophilic vinyl monomer includes but is not limited to any one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate or poly (ethylene glycol) methacrylate, preferably hydroxyethyl acrylate.
[0042] In the present invention, the cross-linking agent is used to form a cross-linked network after the liquid phase component and the solid phase component are mixed and free radical polymerization occurs. It is generally a monomer containing two or more vinyl units, specifically including but not limited to any one or more of polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, diacrylamide polyethylene glycol, dimethylacrylamide polyethylene glycol, dimethacrylate phosphate or diacrylic acid phosphate.
[0043] In the present invention, the reducing agent is used to undergo a redox reaction with the initiator in the solid phase component, thereby generating free radicals to initiate the ring-opening polymerization of the cyclic monomer. Specifically, the reducing agent includes, but is not limited to, any one or more of tertiary amine reducing agents such as N,N-dimethylaniline, N,N-trimethylaniline, and N,N-dimethyl-p-toluidine. The initiator includes, but is not limited to, any one or more of organic peroxides such as benzoyl peroxide, tert-butyl benzoyl peroxide, dibenzoyl peroxide, and diisophorone peroxide.
[0044] In the present invention, the inorganic filler is any one or more of an inorganic salt containing magnesium / calcium elements, an oxide containing magnesium / calcium elements, or bioactive glass, which can be evenly dispersed between the polymer network, and further resist the shrinkage caused by polymerization through the filler effect, which can effectively reduce the shrinkage rate to 0.1~1%. At the same time, in the presence of body fluids, the added inorganic filler can undergo a hydration and curing reaction, and form a skeleton in the cross-linked copolymer to maintain the mechanical properties, or even improve the mechanical properties. Specifically, the inorganic filler includes but is not limited to any one or more of β calcium phosphate, α calcium phosphate, amorphous calcium phosphate, calcium oxide, overburned magnesium oxide, magnesium phosphate of magnesia type, amorphous magnesium phosphate, bioactive glass, potassium dihydrogen phosphate, or diammonium hydrogen phosphate.
[0045] In some embodiments of the present invention, the ratio of the mass of the inorganic filler to the volume of the liquid phase component is 0.1 to 5 g / mL, preferably 0.5 to 2 g / mL.
[0046] Since in the present invention, the hydrophilic vinyl monomer, crosslinking agent, reducing agent and cyclic monomer are generally liquid phase components, they need to be viewed as a whole. In some embodiments of the present invention, the molar ratio of the hydrophilic vinyl monomer, crosslinking agent, reducing agent and cyclic monomer is (0.01-10): (0.001-0.1): (0.001-0.1): 1, preferably (0.5-3): (0.005-0.05): (0.005-0.05): 1. In addition, in the present invention, the molar ratio of the initiator (actually an oxidant) to the reducing agent is (0.1-1): 1, preferably (0.5-1): 1.
[0047] The present invention also provides a method for preparing the above-mentioned low shrinkage self-reinforced degradable bone cement, comprising the following steps:
[0048] The liquid phase component and the solid phase component are mixed and solidified in situ to obtain bone cement.
[0049] It can be seen that the preparation method provided by the present invention is simple, convenient, easy to implement, and is conducive to large-scale or industrial production.
[0050] According to tests, the shrinkage rate of the bone cement provided by the present invention is 0.1-10%, and the degradation rate after 3 months in phosphate buffered saline is 18.7%-26.9%.
[0051] In summary, the low shrinkage self-reinforced degradable bone cement provided by the present invention is formed by in-situ curing after free radical ring-opening polymerization of cyclic monomers in the human body environment, and the reaction process is rapid, slightly exothermic, and will not cause thermal damage to bone tissue. At the same time, the ring-opening polymerization of cyclic monomers can effectively reduce the volume shrinkage during polymerization and curing, reduce the exothermic effect of the polymerization process, and then by adding inorganic fillers, occupy the space of the polymerization reaction, replace part of the polymer, and leave a gap between the polymer and the filler, further reducing the shrinkage rate, so that the subsequent use will not be loose. When the body fluid is encountered in the in vivo environment, the inorganic filler in the solid phase component undergoes a bone cement curing reaction, hinders water intrusion, maintains strength and even mechanical strength increases. In addition, the present invention has degradability because the cyclic monomer generates an ester bond after ring-opening polymerization, can be absorbed by the human body, but the absorption time is longer, avoiding the deficiency of too fast degradation time of traditional calcium phosphate bone cement or magnesium phosphate bone cement. Similarly, the bone cement also has good osteogenic activity, and has important application value in orthopedics and stomatology.
[0052] Based on this, the bone cement product of the present invention has the advantages of low shrinkage, high strength and degradability, as well as low curing exotherm and good osteogenic activity, and can provide an application of the above-mentioned low shrinkage self-reinforced degradable bone cement in the preparation of bone cement products.
[0053] In the present invention, the solid phase component and the liquid phase component are preferably mixed evenly and then filled into a bone cement syringe, and the bone cement during the injection phase is injected into the bone injury site with the assistance of imaging.
[0054] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.
[0055] Example 1
[0056] The liquid phase components are cycloketone acetal MDO (7.8 g), comonomer hydroxyethyl methacrylate (17.2 g), 2 mol% polyethylene glycol dimethacrylate crosslinking agent, and 1 mol% reducing agent N, N-dimethyl-p-toluidine (DMPT), which are mixed evenly and set aside;
[0057] The solid phase components are magnesium phosphate cement (14.4 g) and benzoyl peroxide BPO (0.02 g). The magnesium phosphate cement added is sintered magnesium phosphate (particle size 2.5 μm, 67 wt%) and ball-milled ammonium dihydrogen phosphate (particle size 5 μm, 33 wt%);
[0058] The solid phase components are added to the liquid phase components, mixed and stirred evenly, filled into the bone cement syringe, and the bone cement in the dough stage is injected into the desired location with the assistance of imaging.
[0059] Example 2
[0060] The liquid phase components are allyl sulfone macrocyclic monomer MAS (6.2 g), comonomer hydroxyethyl acrylate (18.8 g), 2 mol% polyethylene glycol diacrylate crosslinker, and 1 mol% reducing agent N, N-dimethyl-p-toluidine (DMPT), which are mixed well and set aside;
[0061] The solid phase components are calcium phosphate cement (14.4 g) and benzoyl peroxide (BPO, 0.02 g). The calcium phosphate cement added is β-tricalcium phosphate (particle size 30 μm, 80wt%) and calcium hydrogen phosphate (particle size 50 μm, 20 wt%);
[0062] The solid phase components are added to the liquid phase components, mixed and stirred evenly, filled into the bone cement syringe, and the bone cement in the dough stage is injected into the desired location with the assistance of imaging.
[0063] Example 3
[0064] The liquid phase components are 5,6-benzo-2-methylene-1,3-dioxepane BMDO (18.0 g), comonomer dimethylaminoethyl acrylate (6.7 g), 2 mol% polyethylene glycol diacrylate crosslinker, and 1 mol% reducing agent N, N-dimethyl-p-toluidine (DMPT), which are mixed evenly and set aside;
[0065] The solid phase components are calcium phosphate cement (14.4 g) and benzoyl peroxide (BPO, 0.02 g). The calcium phosphate cement is 1600 ° C over-burned magnesium oxide (particle size 30 μm, 80 wt%) and potassium dihydrogen phosphate (particle size 50 μm, 20 wt%);
[0066] The solid phase components are added to the liquid phase components, mixed and stirred evenly, filled into the bone cement syringe, and the bone cement in the dough stage is injected into the desired location with the assistance of imaging.
[0067] Example 4
[0068] The liquid phase components are spiro-o-carbonate SOC (18.3 g), comonomer methacrylic acid MMA (8.0 g), 2 mol% polyethylene glycol diacrylate crosslinking agent, and 1 mol% reducing agent N, N-dimethyl-p-toluidine (DMPT), which are mixed evenly and set aside;
[0069] The solid phase components are bioactive glass (45 μm, 14.4 g) and benzoyl peroxide (BPO, 0.02 g). The bioactive glass added is silicate, phosphorus pentoxide and calcium oxide sintered (particle size 100 nm);
[0070] The solid phase components are added to the liquid phase components, mixed and stirred evenly, filled into the bone cement syringe, and the bone cement in the dough stage is injected into the desired location with the assistance of imaging.
[0071] Comparative Example 1
[0072] After mixing the solid and liquid phases of commercially available bone cement OSTEOPAL® evenly according to the instructions for use, fill the bone cement into a syringe and, with the assistance of imaging, inject the bone cement in the dough phase into the desired area.
[0073] Comparative Example 2
[0074] The liquid phase component is cycloketone acetal MDO (7.8 g), the comonomer is hydrophobic n-butyl acrylate BA (17.2 g), 2 mol% polyethylene glycol dimethacrylate crosslinker, 1 mol% reducing agent N, N-dimethyl-p-toluidine (DMPT), which are mixed well and set aside;
[0075] The solid phase components are magnesium phosphate cement (14.4 g) and benzoyl peroxide BPO (0.02 g). The magnesium phosphate cement added is sintered magnesium phosphate (particle size 2.5 μm, 67 wt%) and ball-milled ammonium dihydrogen phosphate (particle size 5 μm, 33 wt%);
[0076] The solid phase components are added to the liquid phase components, mixed and stirred evenly, filled into the bone cement syringe, and the bone cement in the dough stage is injected into the desired location with the assistance of imaging.
[0077] Performance Testing
[0078] (1) Bone cement shrinkage test
[0079] First, take 50 μL of uncured bone cement with a pipette, accurately weigh the mass on a balance, and divide the mass by the volume to determine the density of the bone cement before curing (ρ 前 When the bone cement is transformed into dough and completely solidified, use a balance and density component to weigh the mass of the bone cement in the air and the mass of the bone cement immersed in water in the tray, and calculate the density of the solidified sample (ρ) according to the Archimedean buoyancy principle. 后 ), according to the international standard ISO 3521, using the formula: Curing shrinkage = (1 – ρ 前 / ρ 后 )×100%, where: 前 is the density of bone cement before curing, in g / cm3 ρ 后 is the density of the bone cement after curing, in g / cm 3 The volume shrinkage of bone cement during the curing process can be calculated.
[0080] The shrinkage test of the bone cement obtained in Comparative Examples 1-2 and Examples 1-4 is as follows Figure 1 shown.
[0081] like Figure 1 As shown: the bone cements obtained in Examples 1 to 4 all exhibited a relatively low shrinkage rate, and the bone cement obtained in Example 2 had the lowest shrinkage rate, which could be as low as 0.6%, indicating that the introduction of the ring-opening polymer provided the bone cement with better anti-shrinkage performance; in addition, through the commercially available bone cement of Example 1, it was found that the shrinkage rate of the commercial bone cement was 8%, which was much higher than that of Examples 1 to 4, indicating that the bone cement constructed by the present invention had excellent anti-shrinkage performance.
[0082] (2) Bone cement mechanical properties test
[0083] The mechanical properties of bone cement were tested according to the international standard IS05833-2002. The liquid components in Examples 1 to 4 were mixed with the solid components, and the solid components of the comparative bone cement material were contacted and mixed with the liquid components. The bubbles were expelled after stirring evenly. Then it was immediately sucked into the syringe and injected into a cylindrical mold with a diameter of 4.5 mm and a height of 9 mm. The mold was demolded after curing. The upper and lower surfaces of the sample were polished to be parallel, and the prepared specimen was subjected to a compression test on a universal testing machine (LLOYD LD-5 model, sensor 2.5kN). The loading speed was 1 mm / min, and the test was stopped when the maximum compressive strength reached the peak value and the sample broke. There were 4 parallel samples in each group, and the results were averaged. The results of the compressive strength of bone cement in each group are shown in Figure 2 .
[0084] Repeat the sample preparation conditions to prepare bone cement compression samples with the same liquid and solid components and the same ratio. After soaking in water for a period of time, the mechanical properties were tested according to the international standard IS05833-2002. The loading speed was 1 mm / min, and the loading was continued until the sample broke. Each group had 4 parallel samples, and the results were averaged. The compressive strength results of bone cement in each group after soaking are shown in Figure 2 .
[0085] like Figure 2 As shown, the low shrinkage self-reinforced biodegradable bone cement provided by the present invention has mechanical properties comparable to those of OSTEOPAL® bone cement products. At the same time, since the inorganic filler undergoes hydration and solidification when soaked in water, water intrusion is blocked on the surface of the material, and the compressive strength of the bone cement is maintained or even slightly increased after soaking in water.
[0086] (3) In vitro degradation experiment
[0087] The degradation behavior of bone cement was determined by weight loss after immersion in bone cement. The dried and hardened bone cement (n=4 replicates per group) was washed in 1 mL phosphate buffered saline (PBS) for 3 h (solution was changed every hour) to remove possible salt residues in the pores of the bone cement. Then, the bone cement was dried overnight at 37 °C and weighed (initial mass m1 was determined). Finally, the bone cement was immersed in 2.5 mL PBS solution and stored at 37 °C for 90 days, with PBS changed every three days. After the immersion, the bone cement was removed from the solution, dried overnight, and weighed again (final mass m2 was determined). The degradation rate was calculated by comparing the bone cement before immersion in PBS solution using the formula: degradation rate = (m1-m2)*100%.
[0088] The in vitro degradation tests of the materials in Comparative Examples 1-2 and Examples 1-4 are as follows Figure 3 shown.
[0089] like Figure 3 As shown: the bone cements obtained in Examples 1 to 4 all showed good degradation rates after 90 days in an in vitro physiological environment, and the degradation of the bone cement obtained in Example 1 was the most obvious, with a degradation rate of up to 26.2%, indicating that the introduction of ester groups by MDO ring-opening polymerization provides bone cement with better degradation performance; in addition, the degradation rate of commercial bone cement in Comparative Example 1 was 1.5% after 90 days, and the degradation performance was poor, which was much lower than that of Examples 1 to 4, indicating that the bone cement constructed by the present invention has excellent in vitro degradation performance. In Comparative Example 2, the fully hydrophobic polymer system has poor water absorption and poor degradability, and even if soluble hydrogen phosphate is added, the degradation rate is below 10%.
[0090] (4) Osteogenic activity test
[0091] OCN and OPN osteogenic activity detection: The extraction method was used, and six experimental groups were set up: Comparative Examples 1-2, Examples 1-4. Twelve samples with a diameter of 10 mm and a thickness of 1 mm were prepared in each group, soaked in PBS, and the extract was taken at two time points: 7 days and 14 days. After culturing the cells on agar medium for 2 generations, the extract was added. After the culture time, the old culture medium was removed, washed with PBS 1-3 times, and then RIAP cell lysis solution was added. After the cells were fully lysed, the cell lysate was centrifuged, and the supernatant was taken. The cell OCN and OPN osteogenic activity was detected according to the Bca kit method.
[0092] The osteogenic activity of the bone cement obtained in Comparative Examples 1-2 and Examples 1-4 was detected as follows: Figure 4 and Figure 5 shown.
[0093] like Figure 4 and Figure 5 As shown: the bone cement obtained in Examples 1 to 4, wherein the tested cell OCN and OPN activities are significantly higher than those in Comparative Examples 1 and 2, because the low shrinkage self-reinforced degradable bone cement provided in the present invention adds inorganic fillers such as magnesium phosphate and diammonium hydrogen phosphate with osteogenic activity, and the inorganic fillers with biological activity can be gradually exposed or released as the bone cement degrades in the body, and when in contact with the surrounding tissue environment, promote the growth of osteoblasts and show osteogenic activity. At the same time, compared with Comparative Example 2, the hydrophilic comonomer replaces the hydrophobic comonomer to increase the cell affinity and have better osteogenic activity.
[0094] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A low shrinkage self-reinforced degradable bone cement, characterized in that: The preparation raw materials include liquid phase components and solid phase components; The liquid phase components include cyclic monomers, hydrophilic vinyl monomers, crosslinking agents and reducing agents; the solid phase components include inorganic fillers and initiators.
2. The low shrinkage self-reinforced biodegradable bone cement according to claim 1, characterized in that: The ratio of the mass of the inorganic filler to the volume of the liquid phase component is (0.1-5):1 g / mL; The molar ratio of the initiator to the reducing agent is (0.1-1):1; The molar ratio of the hydrophilic vinyl monomer, the crosslinking agent, the reducing agent and the cyclic monomer is (0.01-10):(0.001-0.1):(0.001-0.1):
1.
3. The low shrinkage self-reinforced degradable bone cement according to claim 1, characterized in that: The molar ratio of the hydrophilic vinyl monomer, the crosslinking agent, the reducing agent and the cyclic monomer is (0.5-3):(0.005-0.05):(0.005-0.05):
1.
4. The low shrinkage self-reinforced degradable bone cement according to any one of claims 1 to 3, characterized in that: The cyclic monomer includes, but is not limited to, any one or more of 2-methylene-1,3-dioxepane, allyl sulfone macrocyclic monomer, 5,6-benzo-2-methylene-1,3-dioxepane or spiro-o-carbonate; The hydrophilic vinyl monomer includes but is not limited to any one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate or poly(ethylene glycol) methacrylate; The reducing agent is but not limited to any one or more of N,N-dimethylaniline, N,N-trimethylaniline, and N,N-dimethyl-p-toluidine; The initiator includes, but is not limited to, any one or more of benzoyl peroxide, tert-butyl benzoyl peroxide, dibenzoyl peroxide or diisophorone peroxide.
5. The low shrinkage self-reinforced degradable bone cement according to any one of claims 1 to 4, characterized in that: The cross-linking agent is a monomer containing two or more vinyl units; The inorganic filler is any one or more of an inorganic salt containing magnesium / calcium elements, an oxide containing magnesium / calcium elements, or bioactive glass.
6. The low shrinkage self-reinforced biodegradable bone cement according to claim 5, characterized in that: The cross-linking agent includes but is not limited to any one or more of polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, diacrylamide polyethylene glycol, dimethacrylamide polyethylene glycol, dimethacrylate phosphate or diacrylate phosphate; The inorganic filler includes, but is not limited to, any one or more of β calcium phosphate, α calcium phosphate, amorphous calcium phosphate, calcium hydrogen phosphate, calcium oxide, overburned magnesium oxide, magnesia phosphate, amorphous magnesium phosphate, bioactive glass, potassium dihydrogen phosphate or diammonium hydrogen phosphate.
7. The low shrinkage self-reinforced degradable bone cement according to any one of claims 1 to 6, characterized in that: The shrinkage rate of the bone cement after curing is 0.1-10%, and the degradation rate after 3 months in phosphate buffered saline is 18.7%-26.9%.
8. A method for preparing a low shrinkage self-reinforced degradable bone cement as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: The liquid phase component and the solid phase component are mixed and solidified in situ to obtain bone cement.
9. Use of the low shrinkage self-reinforced degradable bone cement according to any one of claims 1 to 7 or the low shrinkage self-reinforced degradable bone cement prepared by the preparation method according to claim 8 in the preparation of bone cement products.
10. The use according to claim 9, characterized in that: The bone cement product is filled into the bone injury site during the injection period.